2016
DOI: 10.1016/j.evolhumbehav.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Looming large in others' eyes: racial stereotypes illuminate dual adaptations for representing threat versus prestige as physical size

Abstract: We hypothesize that, paralleling the evolution of human hierarchies from social structures based on dominance to those based on prestige, adaptations for representing status are derived from those for representing relative fighting capacity. Because both violence and status are important adaptive challenges, the mind contains the ancestral representational system as well as the derived system. When the two representational tasks conflict, owing to the exigent nature of potential violence, the former should tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 75 publications
3
48
1
Order By: Relevance
“…Also, the African-Americanesounding names may not have sufficiently tested for potential implicit bias related to race. However, several studies of racial disparities in other fields have used such racially identifiable names to experimentally manipulate race and found significant effects (Bertrand & Mullainathan, 2004;Ewens, Tomlin, & Wang, 2014;Giulietti, Tonin, & Vlassopoulos, 2017;Holbrook, Fessler, & Navarrete, 2016;Okonofua & Eberhardt, 2015). Other methods to reveal implicit bias such as priming tasks or using images and videos may be more salient (Burgess et al, 2008;Green et al, 2007;Mathur, Richeson, Paice, Muzyka, & Chiao, 2014).…”
Section: Limitationsmentioning
confidence: 99%
“…Also, the African-Americanesounding names may not have sufficiently tested for potential implicit bias related to race. However, several studies of racial disparities in other fields have used such racially identifiable names to experimentally manipulate race and found significant effects (Bertrand & Mullainathan, 2004;Ewens, Tomlin, & Wang, 2014;Giulietti, Tonin, & Vlassopoulos, 2017;Holbrook, Fessler, & Navarrete, 2016;Okonofua & Eberhardt, 2015). Other methods to reveal implicit bias such as priming tasks or using images and videos may be more salient (Burgess et al, 2008;Green et al, 2007;Mathur, Richeson, Paice, Muzyka, & Chiao, 2014).…”
Section: Limitationsmentioning
confidence: 99%
“…This could be reconciled with our reinterpretation, to the extent that such feelings are an indirect expression of prosocial attitudes and emotions. Mental representations of size have been shown to index traits relevant to social standing, including prestige [77], so feeling small could be associated with high valuation of others. Although feeling "small" can thus be linked to prosocial behavior, it is not clear that, in general, feeling small is a good fit with approachoriented prosocial motives.…”
Section: Awementioning
confidence: 99%
“…Assumptions can be wrong: Holbrook et al (2015), showed participants rated the same story differently depending on the name of the character. Black-sounding names, Jamal, DeShawn or Darnell, drew negative perceptions about the social status of the character compared to when the name in the same story had "white-sounding names", Connor, Wyatt or Garrett (Holbrook et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Black-sounding names, Jamal, DeShawn or Darnell, drew negative perceptions about the social status of the character compared to when the name in the same story had "white-sounding names", Connor, Wyatt or Garrett (Holbrook et al, 2015). Stereotypical views could interpret signs of authoritativeness, strongmindedness, decisiveness, aggressive, confident, tough, willing to challenge, risk-taking, a problemsolving approach and ability to inspire as masculine behaviour: think leader, think male?…”
Section: Introductionmentioning
confidence: 99%